2021
DOI: 10.1007/s40262-021-01012-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renal Impairment on the Pharmacokinetics of the Dual GIP and GLP-1 Receptor Agonist Tirzepatide

Abstract: Background and AimsThe pharmacokinetics (PK) and single-dose tolerability of tirzepatide, a dual glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1 receptor agonist being developed for once-weekly treatment of type 2 diabetes (T2D), weight management, and nonalcoholic steatohepatitis, was evaluated in subjects with renal impairment versus healthy subjects with normal renal function. Methods Forty-five subjects, categorized by baseline renal status, i.e. mild (n = 8, estimated glomerular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 37 publications
(41 reference statements)
0
40
0
2
Order By: Relevance
“…Urva et al [62] reported the PK and tolerability of TZP in patients with or without T2DM and various degrees of renal impairment compared to healthy subjects. Forty-five subjects (30 men and 15 women) aged 40 to 84 years, with BMI ≥ 19.0 and ≤ 40.0 kg/m 2 , were included in the study.…”
Section: Safety and Tolerability And Other Potential Beneficial Effec...mentioning
confidence: 99%
“…Urva et al [62] reported the PK and tolerability of TZP in patients with or without T2DM and various degrees of renal impairment compared to healthy subjects. Forty-five subjects (30 men and 15 women) aged 40 to 84 years, with BMI ≥ 19.0 and ≤ 40.0 kg/m 2 , were included in the study.…”
Section: Safety and Tolerability And Other Potential Beneficial Effec...mentioning
confidence: 99%
“…Both Cmax and AUC0-inf of tirzepatide exhibit dose proportional pharmacokinetics, and neither hepatic nor renal insufficiency significantly changes Cmax, AUC, or half-life. [7][8][9] Incretin Effect Incretin hormone receptors make effective targets for drug therapy in T2DM because they account for over 50% of the insulin secreted in response to oral glucose. 10 It is now realized that GIP has the strongest insulinotropic actions of the incretin hormones and has little to no activity when diabetes develops.…”
Section: Pharmacokinetics Of Tirzepatidementioning
confidence: 99%
“…Both Cmax and AUC0-inf of tirzepatide exhibit dose proportional pharmacokinetics, and neither hepatic nor renal insufficiency significantly changes Cmax, AUC, or half-life. 7–9…”
Section: Pharmacokinetics Of Tirzepatidementioning
confidence: 99%
“…Second, patients with chronic kidney disease (CKD) with estimated glomerular filtration rate (eGFR) below 45 ml/min/1.73 m 2 were excluded from these trials [5,6]. One study by Urva et al [18] has shown that renal impairment including need for hemodialysis has no clinically relevant effects on pharmacokinetics of tirzepatide. However, the latter investigation was a single-dose study that used tirzepatide in a small dose of 5 mg [18].…”
Section: Limitations Of Tirzepatidementioning
confidence: 99%
“…One study by Urva et al [18] has shown that renal impairment including need for hemodialysis has no clinically relevant effects on pharmacokinetics of tirzepatide. However, the latter investigation was a single-dose study that used tirzepatide in a small dose of 5 mg [18]. Third, patients with diabetic maculopathy and proliferative retinopathy and HbA1c levels > 10.5% were also excluded.…”
Section: Limitations Of Tirzepatidementioning
confidence: 99%